Nonstationary desertification dynamics of desert oasis under climate change and human interference - Huang, Guohe (2016)
Desertification is becoming a major ecological concern in arid and semiarid regions, especially under climate change. Globally, it is burning up lands for human habitats with a rapidly spreading tendency. Many scientists have been struggling to explore the related mechanisms. Challenges remain in revealing the fundamental principle in terms of desert-oasis interactions that are associated with nonstationary variations. Here we present a theory of desertification dynamics through examining nonstationary effects of climate change and human interference. We hypothesize that such dynamics can be described as the fate and transport of dry air mass continuously generated from desert. We simulate a region in northwestern China and reveal that dynamics of the nonstationary desertification process is subject to interactive impacts from a variety of factors. Our study moves forward the field of desertification studies through initiation of the dynamics and nonstationarity concepts which allow the fundamental mechanism to be disclosed.